2018
DOI: 10.1016/j.cbpc.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent light exposure incites acute and prolonged immune responses in zebrafish (Danio rerio) skin

Abstract: Artificial light produces an emission spectrum that is considerably different than the solar spectrum. Artificial light has been shown to affect various behavior and physiological processes in vertebrates. However, there exists a paucity of data regarding the molecular genetic effects of artificial light exposure. Previous studies showed that one of the commonly used fluorescent light source (FL; 4100K or "cool white") can affect signaling pathways related to maintenance of circadian rhythm, cell cycle progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The colour of fish is determined by the type of melanin synthesized, whereby a disturbance of the latter due to different environmental factors cause colour defects (Ferreira & Magina, ). Prolonged exposure of an organism to a fluorescent light may create potential adverse effects on the health of animals such as extracellular damage (skin; Chang et al, ; Gonzalez et al, ). Such changes in skin colour due to light were also observed in False Clownfish Amphiprion ocellaris (Yasir & Qin, ) and Red porgy, Pagrus pagrus (Pavlidis et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The colour of fish is determined by the type of melanin synthesized, whereby a disturbance of the latter due to different environmental factors cause colour defects (Ferreira & Magina, ). Prolonged exposure of an organism to a fluorescent light may create potential adverse effects on the health of animals such as extracellular damage (skin; Chang et al, ; Gonzalez et al, ). Such changes in skin colour due to light were also observed in False Clownfish Amphiprion ocellaris (Yasir & Qin, ) and Red porgy, Pagrus pagrus (Pavlidis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The content of tyrosinase and cysteine, which are the determinants of fish colour can be affected by several factors such as dietary composition (Wang et al, ; Watson, Wayman, Kelley, Feugier, & Biourge, ) and environment cues such as light (Gonzalez et al, ). In this study, we found that artificial photoperiod manipulation affected the contents of tyrosinase and cysteine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature adult male Danio rerio (TU, zebrafish, 3) from the Zebrafish International Resource Center in Eugene, OR, and three mature adult male Oryzias latipes (Cab, medaka) from the Xiphophorus Genetic Stock Center were used for FL exposure (40 min, 35 kJ/m 2 ). All protocols were carried out as previously described [1,13]. Prior to light exposure, fish were placed individually into 100 mL of filtered home aquaria water and kept in the dark for 14 h. FL exposure occurred in UV-transparent cuvettes (9 × 7.5 × 1.5 cm) in 90 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…These experiments [1][2][3][4] and others [5][6][7] were the first to characterize the genetic response of an intact animal to various light sources and/or specific wavelengths. However, they do not directly address the question of how FL induces highly conserved inflammatory and cellular immune responses initiated by the IL1B regulator, in both a direct light receiving organ and internal organs.…”
mentioning
confidence: 99%